Genetic diversity of Rana (Pelophylax) ridibunda and Bufo (Pseudepidalea) viridis in different populations - TAYEBEH MOSLEHI; MAJID MAHDIEH; ALIREZA SHAYESTEHFAR; SEYED MEHDI TALEBI (Biodiversitas Journal of Biological Diversity, 2015)
Moslehi T, Mahdieh M, Shayestehfar A, Talebi SM. 2015. Genetic diversity of Rana (Pelophylax) ridibunda and Bufo (Pseudepidalea) viridis in different populations. Biodiversitas 16: 128-131. In present study, genetic diversity of two genus of Anura order was investigated in Iran. For this reasons, four populations of Rana (Pelophylax) ridibunda (R1-R4) and three populations of Bufo (Pseudepidalea) viridis (B1-B3) were selected from different regions of Arak province. Random Amplified Polymorphic DNA (RAPD) marker was used for molecular investigation. Nine random primers were used that only four of them were suitable and revealing different bands pattern for further analysis. A total of 69 scorable bands (loci) were found. The obtained data were analyzed using MVSP software for clustering. The studied populations were separated from each other in the UPGMA tree as well as PCA and PCOplots. In the mentioned diagrams the populations of B. (Pseudepidalea) viridis were closely together, while the populations of other species were placed far from each other. The results of this study showed that high genetic variations were present among R. ridibunda populations, but this condition was in contrast to B. viridis populations, where these populations were near each other. Key words: Bufo, genetic variations, population, Rana, RAPD.